Original device and approaches to the study of temperature distribution in various eye segments (experimental study) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Today the question of temperature distribution in various eye segments of human and animals remains understudied.Objective. To design the device for measuring intraocular temperature and to study in the experiment the principle of temperature distribution in various segments of rabbit eye. Material and methods. Experiment was carried out on 11 rabbits (22 eyes). For temperature measurement the thermoelectric device was designed, which consists of temperature registration module, measure probes of 0.7 mm in diameter and computer with software.Results. Under ambient temperature 23.8°C, the temperature of various eye segments was the following: posterior fornix of conjunctiva ? 37.41°C; anterior fornix of conjunctiva ? 36.82оС; cornea surface ? 34.41оС; ocular anterior chamber ? 35.97оС; anterior part of vitreous ? 36.96оС; of middle part of vitreous ? 37.40оС; back part of vitreous ? 37.50оС; of retina/ vascular membrane ? 37.64оС; subtenon area ? 37.78оС. Temperature difference of cornea external surface and ocular anterior chamber was 1.56оС, and of cornea external surface and retina was 3.23оС.Conclusion. Thermoelectric device, which helps to make measurements in various eye segments, was designed. Due to this device the temperature distribution in rabbit eye was studied in vivo.
Keywords: thermoelectric device; temperature; thermocouple; rabbit eye